1996
DOI: 10.1142/s0129065796000361
|View full text |Cite
|
Sign up to set email alerts
|

Chaos Control by Electric Current in an Enzymatic Reaction

Abstract: We apply the continuous delayed feedback method of Pyragas to control chaos in the enzymatic Peroxidase-Oxidase (PO) reaction, using the electric current as the control parameter. At each data point in the time series, a time delayed feedback function applies a small amplitude perturbation to inert platinum electrodes, which causes redox processes on the surface of the electrodes. These perturbations are calculated as the difference between the previous (time delayed) signal and the actual signal. Unstable per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In chemistry, classical engineering techniques (e.g., PID control) were adapted to the needs of control of strongly nonlinear systems. The control of chaotic systems in the Belousov–Zhabotinsky reaction, electrochemical, , enzymatic, and gas-phase systems brought attention to the relationships between nonlinear dynamics and control theory through the recognition of importance of unstable phase state objects (e.g., stationary states and limit cycles). In addition to chaos control, the control of spatiotemporal pattern formation in distributed (e.g., BZ reaction , and CO oxidation) and discrete (e.g., electrochemical reactions on electrode arrays and BZ beads) systems showed that novel, complex patterns can be obtained by proper application of a feedback signal.…”
Section: Introductionmentioning
confidence: 99%
“…In chemistry, classical engineering techniques (e.g., PID control) were adapted to the needs of control of strongly nonlinear systems. The control of chaotic systems in the Belousov–Zhabotinsky reaction, electrochemical, , enzymatic, and gas-phase systems brought attention to the relationships between nonlinear dynamics and control theory through the recognition of importance of unstable phase state objects (e.g., stationary states and limit cycles). In addition to chaos control, the control of spatiotemporal pattern formation in distributed (e.g., BZ reaction , and CO oxidation) and discrete (e.g., electrochemical reactions on electrode arrays and BZ beads) systems showed that novel, complex patterns can be obtained by proper application of a feedback signal.…”
Section: Introductionmentioning
confidence: 99%